ANALYSIS OF CONCRETE COMPRESSIVE STRENGTH USING LIGHTWEIGHT BRICKS AS A PARTIAL REPLACEMENT OF FINE AGGREGATE - TETUKO WAHYU JATMIKO; SAHAT MARTUA SIHOMBING; BERMANDO SIAGIAN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Infrastructure development is a top priority in Indonesia due to economic growth and demographic changes. With a budget of 149.81 trillion in 2021, infrastructure development is prioritized for economic recovery from COVID-19. Increased construction activities, including buildings, roads, and bridges, increase the demand for materials such as concrete, which is chosen for its strength and affordable cost. However, excessive sand mining for concrete has a negative impact on the environment. In addition, the increase in construction waste emphasizes the importance of waste management. This study explores the use of lightweight brick waste as a partial substitute for sand in concrete, focusing on its effect on the compressive strength of concrete. The following are the conclusions that can be drawn based on data analysis and discussion regarding the utilization of lightweight brick powder waste with variations of 0%, 12%, and 17% that have been explained in the previous chapter, the results of the compressive strength test on normal concrete at the age of 28 days reached 440 kN (fc'24.91), while variation 1 with 12% lightweight brick substitution reached 345 kN (fc' 19.53), and variation 2 with 17% lightweight brick substitution reached 309 kN (fc'17.49).